Experiential avoidance, coping, and anxiety in students from a public university in Lima - Pablo D. Valencia; José R. Paz; Erick Paredes; Max León; César Zuñe; César Falcón; Roberto Portal; Rosmery Cáceres; Lourdes Murillo (Interacciones)
Experiential avoidance (EA)—or psychological (in)flexibility—is a central concept in contextual therapies, and it has been proposed as a transdiagnostic dimension of psychopathology. We intended to test whether EA and other coping strategies independently predict both state and trait-anxiety. We administered a set of measures (the AAQ-II, a modified version of the Brief COPE, and the STAI) to 284 undergraduates from a public university in Lima, Peru. Results showed that EA, lack of problem solving, self-blame, and substance use were all significantly related to state and trait-anxiety. However, after submitting these variables to multiple regression analyses, only EA, lack of problem solving, and self-blame remained significant predictors of trait-anxiety; of these, only EA made a significant improvement to the model (ΔR² = .16). On the other hand, none of the variables under study were significant predictors of state-anxiety. We concluded that the effort to avoid unpleasant thoughts and emotions constitutes a central aspect of trait-anxiety. We discussed these findings in light of previous studies, and gave suggestions for future research.